2021
DOI: 10.3390/cancers13040657
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Mortality Trends for Cancer Patients with Septic Shock Stratified by Cancer Type from 2009 to 2017: A Population-Based Cohort Study

Abstract: There have been recent advances in both cancer and sepsis management. This study aimed to assess short and long-term mortality trends in cancer patients with septic shock from 2009 to 2017 by cancer type. This nationwide population-based cohort study using data from the National Health Insurance Service of Korea included adult cancer patients who presented to an emergency department (ED) with septic shock from 2009 to 2017. Among 43,466 adult cancer patients with septic shock (90% solid and 10% hematologic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…We previously reported the mortality trends of septic shock in cancer patients with claims data using diagnostic codes [ 16 ]. We used a clinical surveillance definition of septic shock based on concurrent vasopressors, antibiotics, and blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the mortality trends of septic shock in cancer patients with claims data using diagnostic codes [ 16 ]. We used a clinical surveillance definition of septic shock based on concurrent vasopressors, antibiotics, and blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…So, what is the mortality rate for cancer patients in septic shock? To assess short- and long-term mortality trends in septic shock patients with cancer by cancer type, Kim et al examined adult cancer patients presenting to the emergency department with septic shock from 2009 to 2017, and found that among the 43,466 adult cancer patients with septic shock (90% solid and 10% hematologic cancer cases), the 30-day and 1-year mortality rates were 52.1% and 81.3%, respectively ( 9 ). The 30-day mortality rate is basically consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Dimopoulos et al found that a history of stage I or II solid tumors was an independent risk factor for 28-day mortality in sepsis ( 8 ). Further, Kim et al showed that the 30-day and 1-year mortality rates were 52.1% and 81.3% in adult sepsis shock patients with cancer ( 9 ). There is also a lack of relevant research on the effect of dobutamine on septic shock patients with tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease was defined by the presence of diagnostic codes (N03, N05, N165, N18‐9, N250, I12‐3, Z490‐2, Z940, Z992, E102, E112, E132, E142, or T861) 20 . Malignancy was defined as the presence of diagnostic codes (C00–C97) with cancer specific deductible code (V027, V193‐4) from the Health Insurance Review and Assessment Service 21 . The accuracy of the diagnosis algorithm with ICD‐10 codes for comorbidities is 85.0%–94.1% 10,22,23 …”
Section: Methodsmentioning
confidence: 99%
“…20 Malignancy was defined as the presence of diagnostic codes (C00-C97) with cancer specific deductible code (V027, V193-4) from the Health Insurance Review and Assessment Service. 21 The accuracy of the diagnosis algorithm with ICD-10 codes for comorbidities is 85.0%-94.1%. 10,22,23…”
Section: Covariatesmentioning
confidence: 99%